PEMBENTUKAN KARAKTER JUJUR DAN SABAR ANAK USIA DINI PERSEPEKTIF AL-QUR’AN - Amrullah Amrullah (LPPM Sekolah Tinggi Agama Islamm (STAI) Fatahillah Serpong, Tangerang Selatan-Banten, Indonesia, 2020)
Basically, the main purpose of character education is to build a strong nation, where the society has a noble, moral, tolerant and collaborative nature. But lately many cases have happened to students in all circles, especially the decline in morals and morals of students and this can be seen from the many cases that were asked in print or electronic media, worrying is if this character problem is left and not received special attention can cause a decline a nation, even more so if the case of bad character befalls young children and is not immediately dealt with can damage the future of Indonesian children. Therefore the author discusses the formation of honest and patient character early childhood when viewed from the Qur'an, which will be presented here is the view of verses in the character of honesty and patience that produces what attitude to children if done, and how to implement it in teaching.